International change and the stability of multiethnic states : Yugoslavia, Lebanon, and crises of governance - Arfi, Badredine (Indiana University Press, 2005)
Develops a theory of governance for multiethnic states in crisis in the context of international change.
Based on the author's thesis--Southern Illinois University at Carbondale.
Keywords: State, The.; Ethnic conflict.; Cultural pluralism.; International organization.; Security, International.; World politics -- 1945-1989.; World politics -- 1989-; Yugoslavia -- Politics and government -- 1945-1980.; Yugoslavia -- Politics and government -- 1980-1992.; Lebanon -- Politics and government -- 1946-1975.; Cultural Diversity; État.; Conflits ethniques.; Diversité culturelle.; Organisation internationale.; Sécurité internationale.; Politique mondiale -- 1945-1989.; Politique mondiale -- 1989-; Yougoslavie -- Politique et gouvernement -- 1945-1980.; Yougoslavie -- Politique et gouvernement -- 1980-1992.; Liban -- Politique et gouvernement -- 1946-1975.; POLITICAL SCIENCE -- General.; Cultural pluralism; Ethnic conflict; International organization; Politics and government; Security, International; State, The; World politics; Lebanon; Yugoslavia; Minderheitenfrage; Jugoslawien; Libanon; Since 1945